PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PERENCANAAN PAJAK TERHADAP NILAI PERUSAHAAN - Indra Iman Sumantri; Intan Ayu Andini (LPPM Universitas Putera Batam, 2019)
This study aims to determine and provide empirical evidence about the influence of Corporate Social Responsibility and Tax Planning on Company Value in agricultural sector manufacturing companies listed on the Indonesia Stock Exchange in the period 2014-2017. The number of samples used in this study are agricultural sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) and published a complete financial report in 2014-2017 with 18 sample companies obtained using the purposive sampling method. The independent variable of this study is Corporate Social Responsibility measured by calculating the index according to GRI4, Tax Planning which is measured by calculating the effective tax rate, and company value measured by calculating the book price. The results of the study were based on a hypothesis test with a significant level of 5%, the results of this study concluded: Corporate Social Responsibility does not affect the value of the company. Tax planning affects the value of the company. Immediately (together) the variable Corporate Social Responsibility and Tax Planning have a significant effect on Company Value.